2012
DOI: 10.1007/s11104-012-1372-7
|View full text |Cite
|
Sign up to set email alerts
|

The symbiotic recapture of nitrogen from dead mycorrhizal and non-mycorrhizal roots of tomato plants

Abstract: Aims The aim was to quantify the nitrogen (N) transferred via the extra-radical mycelium of the arbuscular mycorrhizal fungus Glomus intraradices from both a dead host and a dead non-host donor root to a receiver tomato plant. The effect of a physical disruption of the soil containing donor plant roots and fungal mycelium on the effectiveness of N transfer was also examined. Methods The root systems of the donor (wild type tomato plants or the mycorrhiza-defective rmc mutant tomato) and the receiver plants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…The predominant nutrient element acquired through AM is phosphorus (P), which is delivered to the plant in its inorganic oxidized form phosphate (P i ) [10] . Furthermore, nitrogen (N) can be transferred to mycorrhizal plants through the fungal symbiont [11] [14] , involving a complex pathway that has been elucidated in considerable detail in recent years [15] [17] . Apart from these central macronutrients, sulfur (S) [18] , [19] and several micronutrients can be delivered to plants through AM fungi [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The predominant nutrient element acquired through AM is phosphorus (P), which is delivered to the plant in its inorganic oxidized form phosphate (P i ) [10] . Furthermore, nitrogen (N) can be transferred to mycorrhizal plants through the fungal symbiont [11] [14] , involving a complex pathway that has been elucidated in considerable detail in recent years [15] [17] . Apart from these central macronutrients, sulfur (S) [18] , [19] and several micronutrients can be delivered to plants through AM fungi [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhang et al [ 45 ] reported similar data, i.e ., higher canopy radius/biomass in M. sativa (alfalfa) plants grown in AM soil as compared to plants grown in fungicide-treated (non-mycorrhized) soil. The growth stimulation can be explained by the increase of P and N content found in AM plants [ 46 49 ]. In this study, the content of N, P and C was also enhanced at 3 wpi in the shoots of AM- when compared to the control plants ( S1 Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Müller et al . 33 found significant translocation of 15 N from dead donor roots to receiver plants in mycorrhizal tomato. Such findings represent evidence of the persistence of ERM viability and functionality in dead root systems, recorded over short periods of time, 2 and 6 weeks, respectively.…”
Section: Discussionmentioning
confidence: 91%